Adolescent Women's Behavior About Premarriage Health Preparation (JURNAL PROTEKSI KESEHATAN, 2022)
The incidence of stunting in Indonesia is still considered high. Considering that the WHO targets the stunting rate to be no more than 20%. Factors that trigger stunting include genetics, behavior, environment and health services. Stunting problem can be prevented by pre-marital preparation in order to change behavior that can lead to improved maternal and child health. This study was to determine the knowledge, attitudes, and actions of adolescent girls about preparing for premarital health. It is a descriptive quantitative method that uses non-probability sampling technique conducted online using a google form. The sample in this study were 70 students of Midwifery, Pasir Pengaraian University. The results of the study showed that adolescent girls who had good knowledge were 52 (74,29%), good attitudes were 54 (77,14%), good actions were 45 (64,29%). The conclusion adolescent girls knowledge, attitudes and actions of premarital health preparation is good category.